MCP‐based detectors: calibration and first photon radiation measurements. (12th July 2019) - Syresin, Evgeny; Grebentsov, Alexander; Brovko, Oleg; Yurkov, Mikhail; Freund, Wolfgang; Grünert, Jan
Abstract : Detectors based on microchannel plates (MCPs) are used to detect free‐electron laser radiation. Three MCP detectors have been developed by JINR for the European XFEL (SASE1, SASE2 and SASE3 lines). Abstract : Detectors based on microchannel plates (MCPs) are used to detect radiation from free‐electron lasers. Three MCP detectors have been developed by JINR for the European XFEL (SASE1, SASE2 and SASE3 lines). These detectors are designed to operate in a wide dynamic range from the level of spontaneous emission to the SASE saturation level (between a few nJ up to 25 mJ), in a wide wavelength range from 0.05 nm to 0.4 nm for SASE1 and SASE2, and from 0.4 nm to 4.43 nm for SASE3. The detectors measure photon pulse energies with an anode and a photodiode. The photon beam image is observed with an MCP imager with a phosphor screen. At present, the SASE1 and SASE3 MCP detectors are commissioned with XFEL beams. Calibration and first measurements of photon radiation in multibunch mode are performed with the SASE1 and SASE3 MCPs. The MCP detector for SASE2 and its electronics are installed in the XFEL tunnel, technically commissioned, and are now ready for acceptance tests with the X‐ray beam.